TSG-6 Activity as a Novel Biomarker of Progression in Knee Osteoarthritis - Wisniewski, Hans-Georg (2013)
OBJECTIVE: To establish whether there is an association between TSG-6 activity and osteoarthritis (OA) progression. DESIGN: TSG-6 activity was determined in 132 synovial fluids from patients with OA of the knee, using a novel quantitative TSG-6 activity assay. The association between TSG-6 activities at baseline and four distinct disease progression states, determined at three-year follow-up, was analyzed using logistic regression. RESULTS: There was a statistically significant relationship between TSG-6 activity at baseline and all OA progression states over a three-year period. Patient knees with TSG-6 activities in the top 10(th) percentile, compared to the median activity, had an odds ratio (OR) of at least 7.86 (confidence interval (CI) [3.2, 20.5]) for total knee arthroplasty (TKA) within three years, and of at least 5.20 (CI [1.8, 13.9]) after adjustment for confounding factors. Receiver operating characteristic (ROC) analysis for knee arthroplasty yielded a cut-off point of 13.3 TSG-6 activity units/ml with the following parameters: area under the curve 0.90 (CI [0.804, 0.996]), sensitivity 0.91 (CI [0.59, 0.99]), specificity 0.82 (CI [0.74, 0.88]) and a negative predictive value (NPV) of 0.99 (CI [0.934, 0.994]). CONCLUSION: The TSG-6 activity is a promising independent biomarker for OA progression. Given the high NPV, this assay may be particularly suitable for identifying patients at low risk of rapid disease progression and to assist in the timing of arthroplasty.